HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN PASIEN RAWAT INAP - Iskandar Markus Sembiring; Novita Br Ginting Munthe (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2019)
Good communication between nurses and patients is one thing in meeting patient needs. Communication in question is therapeutic communication in providing nursing care to patients. The low therapeutic communication carried out by nurses has an impact on patient dissatisfaction. New patients will be satisfied if the performance of the health services they obtain is the same or exceeds their expectations. The general objective of this study is to analyze the relationship between therapeutic communication of nurses and the satisfaction of inpatients. This type of research is quantitative research with the design of the study is descriptive correlation and how to collect data by distributing questionnaires. Sampling technique with purposive sampling technique. The statistical test used is spearman's rho. The results showed that there was a relationship between therapeutic communication of nurses and patient satisfaction, of 36 respondents there were 22 people (61.1%) patients who were dissatisfied with nurse therapeutic communication with a value of P = 0.043, p <Î± (0.05), with a value R = 0.339, then the relationship between therapeutic communication nurses with patient satisfaction is a strong category. Based on the results of this study, it is expected that the deli hospital will improve and conduct training on the implementation of nurse therapeutic communication so that the patient's satisfaction level increases.